Dietary nitrate supplementation very slightly mitigates the oxidative stress induced by high-intensity training performed in normobaric hypoxia - Sousa, Ana; Chambion-Diaz, Marie; Pialoux, Vincent; Carin, Romain; Viana, João Luís; Milheiro, Jaime; Reis, Víctor Machado; Millet, Grégoire (Biology of Sport, 2025)
Oxidative stress is augmented under hypoxic environments, which may be attenuated with antioxidant supplementation. We investigated the effects of dietary nitrate (NO 3 −) supplementation combined with high-intensity training performed under hypoxic conditions on antioxidant/pro-oxidant balance. Thirty trained participants were assigned to one of three groups – HNO: hypoxia (13% F i O 2 ) + NO 3 −; HPL: hypoxia + placebo; CON: normoxia (20.9% Fi O2) + placebo – while performing 12 cycling high-intensity interval training (HIIT) sessions during a 4-week period (3 sessions/week). Before and after the intervention, venous blood samples were collected and a time to exhaustion test (T lim ) was performed (with vastus lateralis changes in local O 2 saturation: SmO 2 monitoring). Glutathione peroxidase (GPX) activity increased in CON ( p = 0.017, ~20%) and superoxide dismutase (SOD), catalase and ferric-reducing antioxidant power (FRAP) did not change in any group. Malondialdehydes (MDA) increased in both HNO ( p = 0.001, ~60%) and CON ( p = 0.023, ~30%) but not in HPL. Advanced oxidation protein products (AOPP), uric acid, and myeloperoxidase activity were not modified by the protocol. Only the CON group recovered faster after the T lim test (SmO 2recovery : p = 0.0003, ~58%). Hypoxic exposure during high-intensity training blunted the increase in GPX and MDA after the intervention period. However, the effects of NO 3 − supplementation seem to very slightly mitigate the detrimental effect of performing high-intensity training under hypoxic conditions.